The Effects of Repeated Exposure to the ARRAY Program With Offenders With Mental Illness - Cox, Robert (Journal of addictions & offender counseling, 2017)
In an A-B-A-B-A single-case research study of 3 incarcerated offenders with mental illness, repeated exposure to the pilot Adult Recidivism Reduction Alternatives (ARRAY) group counseling intervention was an effective or very effective treatment for anxiety, depression, and associated somatic symptoms.